Enzyme-linked immunosorbent assay for streptococcal M protein antibodies. - Russell, H (1976)
The enzyme-linked immunosorbent assay (ELISA) described by Engvall and Perlmann, which uses antigen-coated tubes and enzyme-labeled anti-immunoglobulin, has been used for the detection of antibodies against streptococcal M protein. The antigen used in the assay was obtained by guanidine extraction of type M-12 streptococcal cell walls followed by hydroxyapatite chromatography. This antigen has the capacity to elicit bactericidal antibodies in rabbits. The results show that the ELISA is specific and highly sensitive for the detection of antibodies in rabbit and human antisera. Preliminary results suggest that, when M-12 antigen is used, the antibodies detected by ELISA are the same antibodies detected in the bactericidal test. The assay has been performed with human and rabbit sera. There was a 96% agreement between bactericidal and ELISA results with rabbit sera and 97.5% agreement with human sera. All bactericidal antibody-positive sera tested thus far yielded positive ELISA results.